Impacts of chemical precipitation of phosphorus with polyaluminum chloride in two eutrophic lakes in southwest Finland - Sarvala Jouko; Helminen Harri (Taylor & Francis, 2025)
In an attempt to improve water quality in 2 eutrophic shallow Finnish lakes, Kirkkojärvi and Littoistenjärvi, phosphorus precipitation with polyaluminum chloride was performed in June 2002 and May 2017, respectively. Here we compare the effects of the chemical treatment between the lakes to enhance our understanding of the mechanisms involved and to improve the predictability of similar management actions in the future. All plankton was killed in the treatment, but phytoplankton recovered in 4 weeks and crustacean zooplankton in 2 months. Because removal fishing had not been successful, the chemical dosage in Kirkkojärvi was intentionally set so high that the treatment killed all fish. In Littoistenjärvi, pH was adjusted so that most fish survived. In Kirkkojärvi, the summer phosphorus (TP) and chlorophyll (Chl-a) concentrations 3 years after treatment dropped by 85\% and 88\% compared to those recorded 3 years before treatment. Cyanobacterial biomass declined by 88\%, with only occasional blooms appearing in 3 of 22 years. The average TP and Chl-a of the post-treatment period 2006–2020 indicated substantial improvement in the ecological state from “bad” to “moderate” rating of the EU Water Framework Directive (WFD). In Littoistenjärvi, the corresponding declines due to the Al treatment were 72\% in TP and 87\% in Chl-a concentration, and 92\% in cyanobacterial biomass. Longevity of treatment effects was estimated using the upper boundaries of the WFD quality classes as the target values. Water quality changes followed the internal loading of TP, affected by temperature and pH.